ANALISIS PERBANDINGAN ON-TIME PERFORMANCE MASKAPAI PENERBANGAN ANTARA BANDARA HUSEIN SASTRANEGARA DAN BANDARA INTERNASIONAL KERTAJATI MENGGUNAKAN FLIGHTRADAR24 - Abdillah, rizki Ade; Yuniarti, Endah; Shevilia, Erna (Jurnal Teknologi Kedirgantaraan, 2025)
This study evaluates the impact of the operational transfer from Husein Sastranegara Airport to Kertajati International Airport, focusing on airline On-Time Performance (OTP) before and after the transition. The research utilizes real-time flight data from Flightradar24 and secondary data from Angkasa Pura II to analyze daily flight schedules for one month prior to (October 2023) and after (April 2024) the transfer. The data is processed to determine percentages of on-time performance, delays, and flight cancellations at both airports. Findings reveal that post-transfer, the total number of flights decreased by 5.20%, while on-time performance improved by 8.81%, from 55.78% at Husein Sastranegara Airport to 64.02% at Kertajati International Airport. Additionally, flight delays reduced by 38.56%, suggesting enhanced operational efficiency. However, the number of flight cancellations rose from 0 at Husein Sastranegara Airport to 24 at Kertajati International Airport, indicating challenges in operational adjustment at the new facility. Key factors influencing delays include military aircraft movements, weather conditions, and the operational adjustments required following the airport transfer.